Islamic financial literacy: Determinants, measurement, and outcomes - Dimvy Rusefani Asetya; Sahara Putri Dahlan (Journal of Islamic Economic Insights, 2026)
Islamic Financial Literacy (IFL) has become an important topic at the intersection of financial literacy, Islamic economics, and inclusive development. Although research on IFL has expanded, the field remains conceptually fragmented because studies vary in how they define, measure, and interpret the construct. This article presents a systematic literature review focused on three issues: determinants, measurement, and outcomes of IFL. The review shows that the most recurrent determinants are education, income, religiosity, demographic background, financial experience, and institutional access, although their effects differ across contexts. The literature also reveals substantial diversity in measurement practices. Some studies adapt conventional financial literacy scales, whereas others develop Islamic-specific instruments covering riba, profit-and-loss sharing, zakat, takaful, sukuk, and other Shariah-compliant concepts. This lack of measurement standardization weakens comparability across studies. In terms of outcomes, higher IFL is generally associated with better financial behavior, stronger intention to use Islamic products, improved financial management, greater market discipline, and higher financial well-being. Overall, the review argues that future IFL research requires clearer construct boundaries, more rigorous measurement, and stronger comparative evidence.